Review and evaluation of alternative chemical disposal technologies (National Academy Press, 1996)
In 1994 the National Research Council published Recommendations for the Disposal of Chemical Agents and Munitions, which assessed the status of various alternative destruction technologies in comparison to the Army's baseline incineration system. The volume's main finding was that no alternative technology was preferable to incineration but that work should continue on the neutralization technologies under Army consideration. In light of the fact that alternative technologies have evolved since the 1994 study, this new volume evaluates five Army-chosen alternatives to the baseline incineration system for the disposal of the bulk nerve and mustard agent stored in ton containers at Army sites located in Newport, Indiana, and Aberdeen, Maryland, respectively. The committee assessed each technology by conducting site visits to the locations of the technology proponent companies and by meeting with state regulators and citizens of the affected areas. This volume makes recommendations to the Army on which, if any, of the five technologies has reached a level of maturity appropriate for consideration for pilot-scale testing at the two affected sites.